Faktor-Faktor yang Mempengaruhi Penggunaan Informasi Akuntansi pada UMKM Kecamatan Sungai Serut Kota Bengkulu - Fitranika, Vika; Hara, Elysa Fitriani; Sari, Novita; Wijayanti, Indah Oktari (Politeknik Raflesia Press, 2024)
This study aims to analyze the factors that influence the use of accounting information in MSMEs in Sungai Serut Kecematan, Bengkulu City. The population of this study were all MSMEs in Sungai Serut District, Bengkulu City in 2020-2021, totaling 90 MSMEs. The statistical tool used is SPSS. The results showed that the scale of the business has a positive effect on the use of accounting information, the bigger the business, the more consideration it will provide for MSME owners to be able to use and improve the use of accounting information to be able to support MSMEs in the future.... Business age has a positive effect on the use of accounting information, the longer the age of MSMEs, the longer the business continuity will be and the wider the knowledge about the importance of accounting information, so that this will encourage MSMEs to better understand the importance of using accounting information Education has a positive effect on the use of accounting information, knowledge about the importance of accounting information contained in MSMEs will affect decisions that will be taken later so that the higher the education they have, it will increase the use of accounting information in MSMEs. Accounting training has a positive effect on the use of accounting information, this shows that the owner / financial manager of MSMEs will have the ability to master knowledge about accounting if he participates in accounting training. The more accounting training that is attended will increase understanding of the importance of accounting information and this will encourage MSMEs to use accounting information.